2018
DOI: 10.1159/000487976
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Profiles of Phlegm-Dampness Constitution

Abstract: Background/Aims: Metabolic diseases are leading health concerns in today’s global society. In traditional Chinese medicine (TCM), one body type studied is the phlegm-dampness constitution (PC), which predisposes individuals to complex metabolic disorders. Genomic studies have revealed the potential metabolic disorders and the molecular features of PC. The role of epigenetics in the regulation of PC, however, is unknown. Methods: We analyzed a genome-wide DNA methylation in 12 volunteers using Illumina Infinium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…chromatin organization, as well as many others (Tollefsbol, 2017). Yao et al (2018) suggested that the potential risk for metabolic disorders in individuals with phlegm-dampness constitution (PC) and also they did explain the clinical features of PC with DNA methylation features. Sorghum tissue methylation profiles produced at lower resolution using methylation-sensitiv amplified polymorphism revealed similar findings, with insignificant methylation changes across seven tissues except for the endosperm (Zhang et al, 2011).…”
Section: Role Of Epigenetics and Dna Methylation In Crop Improvementmentioning
confidence: 90%
See 1 more Smart Citation
“…chromatin organization, as well as many others (Tollefsbol, 2017). Yao et al (2018) suggested that the potential risk for metabolic disorders in individuals with phlegm-dampness constitution (PC) and also they did explain the clinical features of PC with DNA methylation features. Sorghum tissue methylation profiles produced at lower resolution using methylation-sensitiv amplified polymorphism revealed similar findings, with insignificant methylation changes across seven tissues except for the endosperm (Zhang et al, 2011).…”
Section: Role Of Epigenetics and Dna Methylation In Crop Improvementmentioning
confidence: 90%
“…The mutual characteristics include of 1) holism-integrity of environment, emotion, and diet with human body; 2) reversibility and balance of yin-yang and epigenetic modifications; 3) dynamic natures and epigenetic changes; 4) visceral manifestation and CM syndrome originated from epigenetic genotype. Epigenetics is considered to be a potential link between postnatal environmental factors and diseases, which refers to a reversible and heritable change that handles gene expression without any alter in the DNA sequence (Yao et al, 2018). An increasing number of epigenomes are now being investigated on crops of high economic value.…”
Section: Traditional Chinese Medicine Epigenetics and Dna Methylationmentioning
confidence: 99%
“…As a reversible epigenetic modification, DNA methylation can be used to explore the influence of postnatal factors on body constitution. Our group previously has applied the Infinium HumanMethylation450 BeadChip technique to explore the DNA methylation profiles of PC; through the DNA methylation research, the molecular mechanism of PC has been partially revealed ( Yao et al, 2018b ). DNA samples were extracted from peripheral blood mononuclear cells of PC and balanced constitution volunteers; the balanced constitution was set to be the control group.…”
Section: Dna Methylation In Constitution Theory and Other Issues Of Chinese Herbal Medicinementioning
confidence: 99%
“…Multiple technologies have been applied in the research of CHM, and fruitful outcomes have been achieved ( Wang et al, 2013 ; Gu and Pei, 2017 ). The recent development of DNA methylation technique sheds new light on the CHM research, and many related studies have also been conducted, which helped to provide a better understanding of some puzzling issues ( Hsieh et al, 2011 ; Liu et al, 2016 ; Yao et al, 2018b ) ( Figure 3 ). In this review, the application of DNA methylation in CHM research will be presented, and specific attention will be placed on its clinical utility; attempts will be made to elucidate the research trends in this field to benefit future studies.…”
Section: Introductionmentioning
confidence: 99%
“…Phlegm-dampness constitution (PC) is one of the various constitution types in TCM, which is considered to be the preclinical stage of various metabolic disorders. Data of the genomic DNA methylation profile in human peripheral blood mononuclear cells of PC and balanced constitution (BC) subjects suggests that DNA methylation can play a role in the pathogenesis of metabolic diseases during the incubation period of HCC [81]. There is a unique methylation level change of the synovium gene in the model of hot arthralgia, and Baihu jiaguizhi decoction can specifically reduce the methylation level of the characteristic gene of hot arthralgia, so as to achieve the effect of treating hot arthralgia [82].…”
Section: Tcm and Dna Methylationmentioning
confidence: 99%